Pengaruh Penggunaan Limbah Plastik HDPE dalam Campuran Aspal AC-BC sebagai Bahan Daur Ulang - ST., MT, Syaifuddin Din; Kurniati, Kurniati; Dahri, Wulan (Jurnal Teknologi, 2025)
The use of plastic waste as an additive in asphalt mixtures presents a promising solution to reduce environmental pollution while enhancing the performance of asphalt mixtures. This study aims to investigate the effect of adding High-Density Polyethylene (HDPE) plastic waste on the Marshall characteristics of Asphalt Concrete – Binder Course (AC-BC) mixtures. Post consumer recycled plastics are being considered for construction to address the threat of plastic waste materials and to improve sustainability. Asphalt pavement construction is highly considered for plastic waste materials recycling due to its large daily production [1]. The HDPE plastic waste used was sourced from household bottle and plastic bag waste, which was shredded and added to the asphalt mixture at variations of 0%, 2%, 4%, 6%, and 8% by asphalt weight. The Marshall method was employed to evaluate stability, flow, Marshall Quotient, Voids in the Mixture (VIM), Voids Filled with Bitument (VFB), and Voids in Mineral Aggregate (VMA). The results indicate that the addition of 6% HDPE yields the most optimal Marshall characteristics, with a stability value of 1367.36 kg, a flow of 3.28 mm, and a Marshall Quotient of 417.09 kg/mm. All parameters at this level met the Bina Marga 2018 specifications. Therefore, the appropriate addition of HDPE waste can significantly improve asphalt mixture quality while contributing to environmental sustainability.